Factors effecting on involvement of nurse leaders in policy making for nursing in Iran: a qualitative study - Aarabi, Akram; Cheraghi, Mohammad Ali; Ghiyasvandian, Shahrzad (International Journal of Advanced Nursing Studies, 2014)
Background: During recent years involvement of Iranian nurse leaders in policy making for nursing has been increased, but still there are many disputations about policy making for nursing in Iran. Objectives: This study intended to explore and describe factors effecting on Involvement of nurse leaders in policy making for nursing in Iran. Method: A qualitative design involving face-to-face, semi-structured interviews by 20 nurse leaders and physicians who had key positions in policy making for nursing had been audio taped and transcribed. Using a conventional content analysis approach, data were analyzed. Results: After open coding and categorizing data three main categories created; include: performance of nurses and nurse leaders; opportunities face to nurse leaders; and conditions governing the healthcare system. Conclusion: Some factors effecting involvement of nurse leaders in policy making for nursing in Iran do not have wide differences with other studies in this field. Although many factors had been mentioned in this study, frequency of codes showed that performance of nurses and nurse leaders acted as a barrier and have had the most effects on involvement. Meanwhile, despite the obstacles, there are abundant opportunities before nurse leaders to making policies and they should apply them to modify these obstacles. Keywords: Health System, Involvement, Iran, Nurse Leaders, Policy Making.